Sector-based midpoint LEACH enhancement for improved energy efficiency and network lifetime - Nirwana Haidar Hari; M. Udin Harun Al Rasyid (National Research and Innovation Agency, 2025)
This study proposes a sector-based, midpoint-driven enhancement of the low-energy adaptive clustering hierarchy (LEACH) protocol to address energy imbalance and inconsistent cluster head (CH) placement in wireless sensor networks (WSNs). Conventional LEACH and its variants often rely on random CH selection and produce uneven cluster geometries, accelerating node depletion and shortening network lifetime. The proposed method divides the network into four sectors and applies a midpoint-guided CH selection mechanism that prioritizes nodes near the geometric center of each sector, thereby shortening intra-cluster communication distances and balancing energy consumption. The protocol is evaluated through Python-based simulation using 100 randomly deployed nodes in a 200×200 m² monitoring area and is compared with several widely used LEACH-based protocols under identical radio and traffic parameters. Key performance metrics include first node death (FND), half nodes death (HND), all nodes death (AND), residual energy, and throughput. Simulation results show lifetime gains of roughly 30–40 % across standard lifetime metrics relative to the original LEACH, while maintaining higher residual energy and stable throughput. These findings highlight the suitability of the protocol for long-duration IoT and smart monitoring applications where energy efficiency is critical.